2003
DOI: 10.1063/1.1590412
|View full text |Cite
|
Sign up to set email alerts
|

Highly resistive GaN layers formed by ion implantation of Zn along the c axis

Abstract: Highly resistive layers are formed by the implantation of Zn ion along the c axis of GaN and AlGaN/GaN epitaxial layers. Heavy ions such as Zn have been desirable for the formation of highly resistive layers, because ions effectively transferred their energy to the crystal atoms rather than the electrons in GaN. A sheet resistance Rs as high as 3.8×1011 Ω/sq was obtained on GaN layers after the ion implantation. Rs increased up to 2.2×1013 Ω/sq after the annealing at 500 °C for 300 s in an N2 atmosphere. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 14 publications
2
26
0
Order By: Relevance
“…[1][2][3][4] Recently, ion-bombardment-produced defects have also been studied in InGaN, AlGaN, and AlN. [5][6][7][8][9][10][11][12][13][14] It has been shown that an increase in In content strongly suppresses dynamic annealing processes ͑i.e., defect migration and interaction processes͒ and enhances the buildup of stable lattice disorder. 8 Interestingly, an increase in Al concentration in the AlGaN alloy has the opposite effect on the efficiency of dynamic annealing, increasing material resistance to ion-beaminduced disordering.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Recently, ion-bombardment-produced defects have also been studied in InGaN, AlGaN, and AlN. [5][6][7][8][9][10][11][12][13][14] It has been shown that an increase in In content strongly suppresses dynamic annealing processes ͑i.e., defect migration and interaction processes͒ and enhances the buildup of stable lattice disorder. 8 Interestingly, an increase in Al concentration in the AlGaN alloy has the opposite effect on the efficiency of dynamic annealing, increasing material resistance to ion-beaminduced disordering.…”
Section: Introductionmentioning
confidence: 99%
“…Implantation isolation have been studied in pure GaN or AlGaN material using H + , He + , N + , F + , Mg + , Ar + , and Zn + ions [2]- [8]. The O + ion implant isolation was also investigated on AlGaAs [9], InAlN [10], and GaN (n-type doping)/GaN materials [11] to study the isolation quality, and P/He, Ar + , and N + ions have been employed in AlGaN/GaN HEMTs [12]- [14].…”
mentioning
confidence: 99%
“…After removing the SiN cap layer in a HF solution, source/drain ohmic contacts were formed by Ti/Al metallization and subsequent rapid thermal annealing at 600 O C for 2 min in an environment of flowing nitrogen. Then device isolation was performed by Zn ion implantation 12 and Ni/Au Schottky gate contact was formed. The fabrication of HEMTs was completed by depositing a SiN dielectric film using catalytic chemical vapor deposition [13][14][15] and subsequent formation of a Ni/Au field plate which was connected to the gate contact at an electrode pad.…”
Section: Introductionmentioning
confidence: 99%